Coordination dynamics and its consequences on sports - Schöllhorn, W. I. (International Journal of Computer Science in Sport, 2003)
The coordination or systems dynamics approach is very often reproached for the usage of fairly sophisticated instruments of analysis, which are only applicable on cyclic movements of single body limbs. In this article the possibility of transferring the coordination dynamics approach on ballistic and whole body movements will be explained by deriving commonalities from rather abstract levels of description. Within the methodological consequences the process oriented approach leads to the identification of highly individual movement patterns. As a rather practical consequence a new movement learning approach is derived which rather puts the focus on the adaptational part of a movement than on the movement itself. A major influence on this approach is given by a change. Several experiments verify the success of this differencial learning approach.